Differentiation of Mycobacterial Species by PCR-Restriction Analysis of DNA (342 Base Pairs) of the RNA Polymerase Gene (rpoB) - Kim, Bum-Joon (American Society for Microbiology, 2001)
PCR amplification-restriction analysis (PRA) of rpoB DNA (342 bp), which comprises the Rif(r) region, was used for the differential identification of 49 mycobacteria. The DNA had been used previously for the identification of mycobacterial species by comparative sequence analysis (B. J. Kim et al., J. Clin. Microbiol. 37:1714–1720, 1999). Digestion with four restriction enzymes (HaeIII, HindII, MvaI, and AccII), which were selected on the basis of rpoB DNA sequences, generated distinctive PRA patterns that allowed not only the reference strains but also the clinical isolates of mycobacteria to be distinguished. Both rapidly and slowly growing mycobacteria were distinctly differentiated by HaeIII digestion of the amplified rpoB DNA. By HindII digestion the Mycobacterium tuberculosis complex was distinguished from the other mycobacteria. Furthermore, six subspecies of Mycobacterium kansasii (subspecies I to VI) as well as the closely related Mycobacterium gastri, and other closely related species, were distinguished by simultaneous digestion of MvaI and AccII. According to the rpoB PRA scheme, 240 strains of clinical isolates could be identified. It was also possible to detect and identify M. tuberculosis directly from sputa and bronchoalveolar lavage specimens. These results suggest that PRA of rpoB DNA is a simple and feasible method not only for the differentiation of culture isolates but also for the rapid detection and identification of pathogenic mycobacteria in primary clinical specimens.